Robust models for the synthesis of flexible palm oil-based regional bioenergy supply chain - Foo, Dominic C. Y. (Animo Repository, 2013)
EFB (Empty fruit bunch) is among the palm oil biomass residues that have been identified as the most abundant bioenergy resources in Southeast Asia. EFB has a good potential to meet the targeted share of renewable energy in this region. This work presents robust LP (linear programming) model to allow for the synthesis of EFB allocation networks that exhibit operational flexibility under multiple biomass supply scenarios. Such multiple scenarios may arise due to many uncertain factors, such as anticipated closure or expansion of mills. A MILP (mixed integer linear programming) extension of the model is then developed. Real life-based case studies of an industrial application are presented to illustrate the use of both variants of the model. © 2013 Elsevier Ltd.